Effect of Crystal Herbal Beverages Characteristics on Consumers’ Buying Decision of Company “X” in The Special Region of Yogyakarta - Nur Afifah; Rika Nalinda; Endah Puspitojati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aimed to investigate the characteristics of instant herbal beverages (i.e. taste, aroma, colors, ingredients, shelf life, and packaging) produced by Company X. In addition, the effects of its characteristics on the Company X customers' decisions to buy the product in Special Region of Yogyakarta was also studied. The study used the statistics descriptive method. The data were then collected using questionnaires. The total sample of this research was 40 people. They were selected using a convenience sampling technique who live in the Special Region of Yogyakarta. The data were analyzed using the multiple linear regression method. The analysis results showed that the taste of instant herbal beverages produced by Company X was in the moderate category. Meanwhile, the aroma, color, ingredients, shelf life, packaging, and customers' decision were in a good category. Simultaneously, the taste, aroma, colors, ingredients, shelf life, and packaging of the product significantly affected the consumers' decisions to buy the product by 57.8%. Partially, the taste, colors, and shelf life significantly affected the consumers' buying decision of instant herbal beverages produced by Company X.